Centre of pressure output in a kinematically driven finite element footstrike model - Hannah, I.; Harland, A.; Price, D.; Lucas, T. (Procedia Engineering, 2012)
A dynamic finite element model of a shod footstrike was developed and driven with six degree of freedom kinematic boundary conditions calculated from a motion capture running trial. Linear tetrahedral elements were used to mesh the midsole and outsole of the footwear with material models determined from appropriate mechanical tests. The model was validated by comparison to experimental high speed video footage and vertical ground reaction force. 92% of model centre of pressure (COP) output readings were found to fall within an experimental error tolerance of ± 20 mm. To investigate the sensitivity of COP output location to the footwear's initial orientation the position of the floor instance was altered by translating ± 2 mm vertically and rotating ± 1° about the sagittal and frontal axes. In comparison to the base model, COP output was found to be most sensitive to rotation about the sagittal axis with a maximum change in location of 69 mm. Output location was altered by up to 26 mm and 19 mm for vertical translation and rotation about the frontal axis respectively. These values are significant and draw into question the validity of the loading conditions that can be applied with a kinematically driven footstrike model.